A study of clinical profile and factors affecting mortality in patients with acute on chronic liver failure in a tertiary hospital in north east India - Bhattacharyya, Mallika; Barman, Narendra Nath; Goswami, Bhabadev; Choudhury, Bikash Narayan (International Journal of Research in Medical Sciences, 2021)
Background: Data regarding Acute on Chronic Liver Failure (ACLF) patients from North East India is scarce and presentation to hospital is often late. We aim to study their clinical profile, aetiology of underlying chronic liver disease, precipitating factors, predictors of mortality and their short term outcome (3 months). Methods: Among 1000 consecutive patients of any form of acute decompensation, 245 patients diagnosed as ACLF were prospectively studied. Comparison was done between survivors versus non survivors of ACLF and between ACLF and Non ACLF patients. Results: Mean age of ACLF patients was 44.2±10.3 years and male:female ratio was 13.4:1. Common causes of underlying cirrhosis in ACLF was alcoholic liver disease, 210 (85.7%), Hepatitis B virus related cirrhosis, 20 (8.2%), Hepatitis C virus related cirrhosis, 6 (2.4%) and cryptogenic in 8 (3.3%). Precipitating causes were alcoholic hepatitis in 98 (46.6%) among alcoholic cirrhosis, acute flare of Hepatitis B infection in 12 patients (60%) among Hepatitis B related cirrhosis, recent use of drugs in 110 (44.8%), sepsis in 71 (28.9%), spontaneous bacterial peritonitis (SBP) in 36 (14.7%), urinary tract infection in 36 (14.7%), acute hepatitis A in 5 (2%) and acute hepatitis E in 3 (1.2%). hepatic encephalopathy, low sodium, high International Normalised Ratio (INR) were found to be significantly associated with high mortality. Increasing number of organ failures is associated with increasing risk of death. Conclusions: ACLF is characterized by rapid deterioration especially when multiorgan failure sets in due to certain precipitating factors in a previously diagnosed or undiagnosed chronic liver disease.